Differentiation of Pathogenic Th17 Cells Is Negatively Regulated by Let-7 MicroRNAs in a Mouse Model of Multiple Sclerosis - Angelou, Constance C.; Wells, Alexandria C.; Vijayaraghavan, Jyothi; Dougan, Carey E.; Lawlor, Rebecca; Iverson, Elizabeth; Lazarevic, Vanja; Kimura, Motoko Y.; Peyton, Shelly R.; Minter, Lisa M.; Osborne, Barbara A.; Pobezinskaya, Elena L.; et al. (Frontiers in Immunology, 2020)
Multiple sclerosis (MS) is a disabling demyelinating autoimmune disorder of the central nervous system (CNS) which is driven by IL-23- and IL-1β-induced autoreactive Th17 cells that traffic to the CNS and secrete proinflammatory cytokines. Th17 pathogenicity in MS has been correlated with the dysregulation of microRNA (miRNA) expression, and specific miRNAs have been shown to promote the pathogenic Th17 phenotype. In the present study, we demonstrate, using the animal model of MS, experimental autoimmune encephalomyelitis (EAE), that let-7 miRNAs confer protection against EAE by negatively regulating the proliferation, differentiation and chemokine-mediated migration of pathogenic Th17 cells to the CNS. Specifically, we found that let-7 miRNAs may directly target the cytokine receptors Il1r1 and Il23r, as well as the chemokine receptors Ccr2 and Ccr5. Therefore, our results identify a novel regulatory role for let-7 miRNAs in pathogenic Th17 differentiation during EAE development, suggesting a promising therapeutic application for disease treatment.